Interaction diagrams for concrete shear wall reinforced with encased steel profiles - Phadnis, P.P.; Karjinni, V.V. (Journal of Structural Engineering, 2024)
Axial force-moment interaction of Steel-Concrete Composite Shear Wall (SCCMSW) under seismic loading is thefocus of present study. Conventional Reinforced Concrete Shear Wall (RCSW) is made composite by embeddingvertical steel sections in the end zone. Current literature shows that, such composite sections are not addressed indeveloping countries codes. A new extended method to develop axial force-moment (P-M) interaction for SCCMSW,based on Eurocode 4 (2004) has been proposed and the results were compared with that obtained from SAP2000 v14program for validation. Nonlinear static analysis has been performed to study damage pattern. It is concluded that theperformance of frame with SCCMSW system is more efficient in terms of lateral stiffness and ductility than RCSW.